PENGARUH MATEMATIS JUMLAH MAHASISWA UNIVERSITAS TERBUKA TERHADAP ANGKA PARTISIPASI KASAR PERGURUAN TINGGI TIAP PROVINSI DI INDONESIA - Nuramaliyah, Nuramaliyah; Safitri, Emeylia; Faulina, Ria (LPPM Universitas Bina Bangsa, 2024)
Education is a key determinant of the quality of human resources in Indonesia. One indicator used to measure educational participation in a region is the Gross Enrolment Ratio (GER). This study focuses on analyzing the influence of the socio-economic conditions of the population and the number students of Universitas Terbuka on the Gross Enrolment Ratio for higher education (GER-HE) in Indonesia. The aim of this research is to analyze the factors that influence the Gross Enrolment Ratio for higher education in several regions. This study uses a quantitative research design with a regression panel data approach. The study area covers all provinces in Indonesia, comprising 34 provinces. The data used in this study is secondary data obtained from the Badan Pusat Statistik (BPS) for the years 2018-2022, including data on GER-HR, poverty indicator, the number of higher education institutions, and expenditure per capita for each province. Additionally, data was sourced from DAAK-UT to obtain the number of Universitas Terbuka students for the years 2018-2022. Based on the results of the Fixed Effect Model (FEM) panel data regression with individual/cross section effects, the factors that influence the GER-HR value are the number of new UT students and per capita expenditure. The number of new UT students has a positive effect while per capita expenditure has a negative effect on GER-HE in Indonesia. Then for variables that have no effect are the number of universities, and per capita expenditure.